Relationship between bullying behavior, gender, bullies and victims among primary school students in the state of Johor - Bhaskaran, Shalini N. (2021)
The purpose of this research is to study relationship between bullying behavior, gender, bullies and victims among primary school students. Bullying issues are usually undetected and reported because many people see bullying as an unnatural part of their lives, especially in primary school, because most people think it is normal for children to fight and learn how to protect themselves hard. This study aimed to determine the level of bullying and gender differences. The study involved 132 respondents at four selected Malay medium national primary schools at Kluang, Johor areas. The respondents were consisted of both male and female who from Year 5. The survey data was gathered using modified School Life Survey by Chan, Myron and Crawshaw (2005) and Peer Interactions in Primary School Questionnaire originated by Thomas Tarshis, MD (2007). The collected data was then analysed thoroughly by score of descriptive statistics (frequency and percentage) and inferential statistics (Mann-Whitney U Test and Spearman Correlation). Overall the findings show the level of bullying and victimization are low and there is no gender differences in bullying. However, there are significant differences in some types of bullying behaviour and there is a significant relationship between bullying and victimization. The significant findings in this study imply that future research on the issue of bullying behaviour, should be carried out with more improvement based on the recommendations discussed.